The Relationship between Family Support and Self-care in Stroke Patients - Setyoadi Setyoadi; Bintari Kusumaningrum; Taramita Purbandari; Dina Ismail (Jordan University of Science and Technology, 2024)
Background: Stroke is caused by a disruption in blood flow to the brain. Some people die from a stroke, while others are left with disabilities that reduce their self care, requiring assistance from others to meet their daily needs. The family becomes a crucial source of support when a patient is at home. Objective: This study examines the correlation between family support and self-care in stroke patients. Methods: The study employed an analytic observational design with a cross-sectional approach. The samples included families and stroke patients. Samples were selected using non-probability purposive sampling, with a sample size of 75 for each group. The instruments used for data collection were the Family Support Questionnaire and the Barthel Index questionnaire. Data were analyzed using descriptive and Spearman’s rank test. Results: The characteristics of stroke patients indicate an average age of 52 years, with an average time since suffering a stroke being 4.1 months. The gender distribution among patients is nearly equal. Family caregivers, with an average age of 43 years, also show a balanced gender distribution, and the majority (49.3%) are partners. Concerning the support received from family caregivers, patients commonly receive emotional and instrumental support. The analysis revealed a Spearman’s correlation coefficient of p<0.05. Conclusion: This study illustrates the importance of family support in helping to improve self-care for patients with stroke undergoing outpatient care and receiving home care from family caregivers. Implications for Nursing: Discharge planning for stroke patients receiving outpatient care needs to highlight the significance of family competence in assisting with home care to enhance patient self care.